PENGARUH LINGKUNGAN KERJA DAN PENGEMBANGAN KARIER TER-HADAP KEPUASAN KERJA PEGAWAI DINAS PARIWISATA KABUPATEN BULELENG, BALI - Ni Wayan Bella Honey; Komang Krisna Heryanda; I Gusti Ketut Adi Winata (STKIP Subang, 2026)
This study aims to analyze the effect of work environment and career development on employee job satisfaction at the Tourism Office of Buleleng Regency, Bali. The study was motivated by the strategic role of public tourism institutions in supporting regional tourism services and by practical issues related to workplace facilities, internal communication, and career development opportunities. A quantitative causal approach was applied. The population consisted of employees of the Tourism Office of Buleleng Regency, and 104 respondents were selected using a total sampling technique based on predetermined criteria. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS 30.0. The analysis included instrument testing, classical assumption testing, partial testing, simultaneous testing, and coefficient of determination analysis. The results show that the work environment has a positive and significant effect on job satisfaction, with a regression coefficient of 0.383 and a significance value of 0.000. Career development also has a positive and significant effect on job satisfaction, with a regression coefficient of 0.469 and a significance value of 0.000. Simultaneously, work environment and career development significantly affect job satisfaction, with an F value of 30.441 and an R Square value of 0.376. These findings indicate that improving workplace conditions and strengthening structured career development programs are important strategies for increasing employee job satisfaction in public-sector tourism organizations.